(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2020)
The present article has the purpose to offer an analysis of the evolution of chilean painting during the 19th century, investigated from the interpretation of the water in the pictorial production of three of the most representative artists in the field of landscape, sea and naval glory painting. In particular, we will refere to the creations of Antonio Smith, Charles Wood and Thomas Somerscales, whose representations of rivers, lakes and especially Pacific Ocean are a proof of the productive phase that in 19th century painting had in Chile. We will focus on the study of the three keys of composition, light and color in a combination of works kept in precious public and private collections, selected due to the judgment about the relevant technical and esthetic qualities by the actual artistic critics and historiography.